After Yugoslavia: Identities and Politics Within the Successor States - AK Baeva-Motusic (Slovo, 2012)
Baeva-Motusic, AK (2012) After Yugoslavia: Identities and Politics Within the Successor States. Edited by ROBERT HUDSON and GLENN BOWMAN. Pp. 264. Basingstoke: Palgrave Macmillan. 2012. £57.50. Hardback. ISBN 9780230201316. [Review]. Slovo, 24 (2). Click here to read the review.